Psychodiagnostic approach to security of students’ psychosomatic health - Korniyenko О. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
In the present article includes research data 2006–2009 years individual-psychological psychosomatic students-girls (375 persons) and students-boys (311 persons) of three faculties of Taras Schevchenko National University of Kyiv: psychology, sociology, radiophysics.